HYDROMECHANICAL COUPLING IN GEOLOGIC PROCESSES - Neuzil C.E. (My University, 2003)
Earth's porous crust and the fluids within it are intimately linked through their mechanical effects on each other. This paper presents an overview of such "hydromechanical" coupling and examines current understanding of its role in geologic processes. An outline of the theory of hydromechanics and rheological models for geologic deformation is included to place various analytical approaches in proper context and to provide an introduction to this broad topic for nonspecialists. Effects of hydromechanical coupling are ubiquitous in geology, and can be local and short-lived or regional and very long-lived. Phenomena such as deposition and erosion, tectonism, seismicity, earth tides, and barometric loading produce strains that tend to alter fluid pressure. Resulting pressure perturbations can be dramatic, and many so-called "anomalous" pressures appear to have been created in this manner. The effects of fluid pressure on crustal mechanics are also profound. Geologic media deform and fail largely in response to effective stress, or total stress minus fluid pressure. As a result, fluid pressures control compaction, decompaction, and other types of deformation, as well as jointing, shear failure, and shear slippage, including events that generate earthquakes. By controlling deformation and failure, fluid pressures also regulate states of stress in the upper crust. Advances in the last 80 years, including theories of consolidation, transient groundwater flow, and poroelasticity, have been synthesized into a reasonably complete conceptual framework for understanding and describing hydromechanical coupling. Full coupling in two or three dimensions is described using force balance equations for deformation coupled with a mass conservation equation for fluid flow. Fully coupled analyses allow hypothesis testing and conceptual model development. However, rigorous application of full coupling is often difficult because (1) the rheological behavior of geologic media is complex and poorly understood and (2) the architecture, mechanical properties and boundary conditions, and deformation history of most geologic systems are not well known. Much of what is known about hydromechanical processes in geologic systems is derived from simpler analyses that ignore certain aspects of solid-fluid coupling. The simplifications introduce error, but more complete analyses usually are not warranted. Hydromechanical analyses should thus be interpreted judiciously, with an appreciation for their limitations. Innovative approaches to hydromechanical modeling and obtaining critical data may circumvent some current limitations and provide answers to remaining questions about crustal processes and fluid behavior in the crust.
Keywords: HYDROMECHANICS; POROELASTICITY; GROUNDWATER HYDRAULICS; RHEOLOGY; DEFORMATION